Analysis of heavy metals in cow-milk based infant formula by inductively coupled plasma - optical emission spectrometry / Nur Syamimi Zainudin and Khairunisa Mohd Zamli - Zainudin, Nur Syamimi; Mohd Zamli, Khairunisa (Universiti Teknologi MARA Cawangan Pahang, 2021)
Most of dairy products especially milk is very popular all over the world. It is consumed daily as it is considered as a nutritionally balanced food and is a major source of the nutrients for infants in the first six months of life. Infant milk formulas are intentionally manufactured to supply essential elements in the diets of newborns. These elements are necessary for biological process and play an important role in the development of infants. However, some of these essential elements become toxic when their concentrations exceed the permissible limit and this creates significant health effects to infants. In this study, the concentration of Cadmium (Cd), Copper (Cu), Nickel (Ni), Lead (Pb) and Zinc (Zn) for seven different brands of infant formulas which are retailed in the Malaysian market were analyzed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). From the results obtained, Zn has the highest concentration in infant formulas followed by Cu, Pb, Ni and Cd. The concentration of Zn, Cu, Pb and Ni were from 0.3467 mg/kg to 0.9833 mg/kg, 0.1433 mg/kg to 0.2533 mg/kg, 0.0133 mg/kg to 0.0267 mg/kg and 0.0033 mg/kg to 0.0100 mg/kg, respectively for all seven different brands of the infant milk formulas. For Cd, the concentration was below the detection limit of the instrument. All heavy metals content in infant formulas were within the permissible limit. The obtained results were compared to an existing standard of permissible amounts of toxic heavy metals in infant milk formulas and with previous literatures.